Factors related to career indecision in a sample of junior college students - Lim, Hoang Hoang. (2009)
This study investigated the phenomenon of career indecision in a sample of 337 students from three Junior Colleges (11th and 12th Graders). Junior College students were selected because they represented the best and the brightest of Singapore's school population, and faced the most important and imminent transition into the world of work. The study explored the extent and degree of career indecision amongst the students and their career decision statuses. Further, it examined whether the variables, namely, vocational identity, the need for occupational information and parental influence related to career indecision. The characteristics which distinguished career decided students from students with career indecision were also investigated.